2019
DOI: 10.1002/jcph.1474
|View full text |Cite
|
Sign up to set email alerts
|

First‐in‐Human Study to Assess the Safety, Pharmacokinetics, and Pharmacodynamics of an Oral Formulation of DS‐1040, an Inhibitor of the Activated Form of Thrombin‐Activatable Fibrinolysis Inhibitor, in Healthy Subjects

Abstract: DS‐1040, a low‐molecular‐weight imidazole derivative, inhibits the enzymatic activity of thrombin‐activatable fibrinolysis inhibitor (TAFIa), enhancing endogenous tissue plasminogen activator–triggered fibrinolysis. This first‐in‐human, randomized, placebo‐controlled, phase 1 study evaluated the safety, pharmacokinetics (PK), and pharmacodynamics (PD) of an oral formulation of DS‐1040. Healthy adults (aged 20‐45 years; N = 56) were randomized 3:1 to receive DS‐1040 orally administered as single ascending doses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 18 publications
2
10
0
Order By: Relevance
“…The interest in a CPU inhibition strategy for application in AIS treatment is rising. 20,33 In the current study, a clear activation of the CPU system after ischemia induction was observed, both in saline-treated and tPA-treated rats, with peak CPU activities at the end of the treatment, followed by a progressive return to baseline levels. CPU peak activities were higher in tPA-treated rats compared to saline-treated animals.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…The interest in a CPU inhibition strategy for application in AIS treatment is rising. 20,33 In the current study, a clear activation of the CPU system after ischemia induction was observed, both in saline-treated and tPA-treated rats, with peak CPU activities at the end of the treatment, followed by a progressive return to baseline levels. CPU peak activities were higher in tPA-treated rats compared to saline-treated animals.…”
Section: Discussionsupporting
confidence: 55%
“…However, the inhibition of CPU (alone or in combination with tPA) was not associated with such a bleeding risk in our study. Furthermore, several other CPU inhibitors were not associated with bleeding complications 17,20,33,46 . Similarly, AZD9684 proved to be safe in patients with pulmonary embolism 47 .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…DS-1040 [(2S)-5-amino-2-[[1-(4-methylcyclohexyl)imidazol-4-yl]methyl]pentanoic acid] was developed by Daiichi Sankyo for the treatment and secondary prevention of AIS and acute PE [52,53]. It showed high selectivity for CPU over CPN (510.000-fold) and was 10-fold more potent than PTCI [165].…”
Section: Potential Benefit Of the Use Of Cpu Inhibitors-overview On Imentioning
confidence: 99%
“…Most recently, a low-molecular weight oral TAFIa inhibitor, DS-1040, was suggested as a potential therapeutic agent to enhance fibrinolysis with low bleeding risk [159]. Interestingly, DS-1040 has been further evaluated in a phase 1 human study in order to assess safety (including bleeding time), tolerability, pharmacokinetics and pharmacodynamics [160].…”
Section: Targeting Tafimentioning
confidence: 99%